Devlet liselerinde görev yapan öğretmenlerin öz yeterlilik inançları ile değişime direnme davranışları arasındaki ilişkinin incelenmesi - Gündüz, Ayşegül (My University, 2017)
Bu araştırmanın temel amacı, devlet liselerinde görev yapan öğretmenlerin öz yeterlilik inançları ile değişime direnme davranışları arasında ilişkiyi ortaya çıkarmaktır. Nicel tarama modeline uygun olarak düzenlenen araştırmanın evreni, 2014 yılında İstanbul ili Anadolu yakasındaki Tuzla ve Pendik ilçelerinde bulunan okulların fiziki altyapı, donanım, öğrenci profilleri bulundukları sosyal çevrenin gelişmişliği dikkate alınarak seçilmiş devlet liselerinde görevli öğretmenlerden oluşmaktadır. Araştırmada rasgele örneklem seçimi metotu ile 451 öğretmene ulaşılmıştır. Araştırmacı anketleri araştırmaya katılan öğretmenlerin okullarına giderek uygulamıştır.

The main purpose of this research is to reveal the relationship between the self-efficacy beliefs of teachers working in state high schools and their behavior of change resistance.The universe of the research that is organized in accordance with the quantitative screening model is composed of the teachers working in the state high schools selected by taking into account the development of the social infrastructure of the physical infrastructure, equipment and student profiles of the schools located in the provinces of Tuzla and Pendik (in Anatolia side of Istanbul) in 2014. In the study, 451 teachers were reached by random sample selection method. Researcher surveys have been increasingly implemented in schools of teachers participating in the research.Literature survey method was used in the theoretical part and survey method was used as data collection tool in the application part of the research. Three measuring instruments were used to collect the data required for this study. These are (1) Personal Information (2) Variable Resistance Scale and (3) Teacher Self-Efficacy Sca
Keywords: Change resistance; Değişime direnme; Denetim; Eğitim ve öğretim; Lise öğretmenleri; Öğretmenler; Öz yeterlilik inancı High school teachers; Self - sufficiency belief; Türkiye; Yetıstirme